A note on the machinability of ultra high tensile steel - Purcell, J. (College of Aeronautics, 1957)
The requirements of this investigation were to determine optimum tool geometry and cutting conditions for turning Ultra High Strength Alloy Steel (fully heat treated to 120 tons per sq.ins.). The material will be used for bolts, whose screw threads will be produced by thread rolling. Dimensional accuracy required on the blanks is 0.0002". The material in the above state presents extremely severe conditions, especially on the nose of the turning tool, and results in rapid wear and loss of dimensional accuracy. Application of cutting coolants or lubricants made no measurable improvement on tool nose wear, benefits gained from the use of coolants being confined to reduction of flank wear.